Spotted fever group rickettsial infection in dogs and their ticks from domestic-wildlife interface areas in southeastern Brazil - Campos, Sabrina Destri Emmerick; Cunha, Nathalie Costa da; Machado, Camila de Souza Cerqueira; Nadal, Niara Vanat; Seabra Junior, Eloy Silva; Telleria, Erich Loza; Cordeiro, Matheus Dias; Toma, Helena Keiko; Almosny, Nádia Regina Pereira (Revista brasileira de parasitologia veterinaria, 2020)
Rickettsia rickettsii is the causative agent of Brazilian spotted fever (BSF), for which humans and dogs are both susceptible. Dogs are sentinels in serological surveys, however, canine disease is rarely reported. Therefore, we aimed to evaluate natural infection by spotted fever group (SFG) Rickettsia spp. in dogs and ticks collected from domiciles close to forest fragments, featuring domestic-wildlife interface areas. Samples from 115 dogs and 135 ixodids were assessed by polymerase chain reactions (PCR) targeting the gltA gene for Rickettsia spp. and the ompA gene for the SFG rickettsial species. One dog (0.87%; 1/115) was positive for R. rickettsii. This dog presented nonspecific laboratory and clinical abnormalities (thrombocytopenia, hyperproteinemia, lymph node enlargement, emaciation, anorexia, and lethargy). Rickettsia parkeri was identified in 2.96% (4/135) of the ticks (Amblyomma sculptum, A. aureolatum, and Rhipicephalus sanguineus). This study confirmed the presence of SFG bacteria in non-endemic and preserved locations, where domestic and wild populations interact. We reinforce the fact that the dog is susceptible to natural R. rickettsii infection. Although this is a rare finding, preventive measures should be taken against BSF in the studied areas. Finally, R. parkeri infection is possibly being demonstrated in A. sculptum for the first time.
Keywords: protilátky bakteriální; Animals; Rickettsia; Spotted Fever Group Rickettsiosis; polymerázová řetězová reakce; Polymerase Chain Reaction; Brazil; nemoci psů; Dog Diseases; Dogs; skvrnité horečky; Antibodies, Bacterial; klíšťata; Ticks; Male; Brazílie; mužské pohlaví; zvířata; psi